A Retrospective Study of Intracranial Pressure in Head-Injured Patients Undergoing Decompressive Craniectomy: A Comparison of Hypertonic Saline and Mannitol - Cheng, Feng; Xu, Min; Liu, Hua; Wang, Wenming; Wang, Zhimin (Frontiers in Neurology, 2018)
Objective: The impact of hypertonic saline (HTS) on control of increased intracranial pressure (ICP) in head-injured patients undergoing decompressive craniectomy (DC) is yet to be established. The current retrospective study was carried out to compare the effect of HTS versus mannitol on lowering ICP burdens in these patients. Methods: We reviewed data on TBI patients admitted between January 1, 2012, and August 31, 2017. Patients after DC who received only 1 type of hyperosmotic agent, 3% HTS or 20% mannitol, were included. Daily ICP burden (hours/day) and response to hyperosmolar agent were used as primary outcome measures. The numbers of intensive care unit days, numbers of hospital days and 2-week mortality rates were also compared between the groups. Results: 30 patients who received 3% HTS only and 30 who received 20% mannitol only were identified for the approximate matching and additional data analyses. The demographic data of the patients were comparable between the 2 groups. The daily ICP burden was significantly lower in the HTS group than in the mannitol group (0.89±1.02 hours/day vs 2.11±2.95 hours/day, respectively; P = 0.038). The slope of fall in ICP in response to a bolus dose at a baseline value of ICP was higher with HTS compared to mannitol (p = 0.001). However, the 2-week mortality was not statistically significant (2 [HTS] vs 1 [mannitol]; P = 0.554). Conclusion: When used in equiosmolar doses, reduction in ICP with 3% HTS is favorable to that with 20% mannitol in TBI patients after DC. However, these superiorities do not seem to confer any additional benefit terms of short-term mortality.